Which example correctly demonstrates polynomial

  1. Which example correctly demonstrates polynomial addition
    1. answers icon 1 answer
    2. views icon 28 views
  2. which example correctly demonstrates polynomial addition(2x^2+6x+1)+(3x^2+3x+9)=-x^2+3x-8 (2x^2+6x+1)+(3x^2+3x+9)=5x^2+9x+10
    1. answers icon 1 answer
    2. lol asked by lol
    3. views icon 14 views
  3. Which example correctly demonstrates polynomial subtraction?A. (2x^2+6x+1)-(3x^2+3x+9)= 5x^2+9x+10 B. (2x^2+6x+1)-(3x^2+3x+9)=
    1. answers icon 1 answer
    2. LAYLA M asked by LAYLA M
    3. views icon 12 views
  4. Which example correctly demonstrates polynomial addition?A) (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10 B) (2x^2 + 6x +
    1. answers icon 1 answer
    2. views icon 14 views
  5. Which example correctly demonstrates polynomial subtraction?A) (2x^2 + 6x + 1) - (3x^2 + 3x + 9) = x^2 + 3x + 8 B) (2x^2 + 6x +
    1. answers icon 1 answer
    2. views icon 57 views
  6. Which example correctly demonstrates polynomial addition?A, (2x^2+6x+1) + (3x^2+3x+9)=-x^2+3x-8 B, (2x^2+6x+1) + (3x^2+3x+9)=
    1. answers icon 1 answer
    2. daniii asked by daniii
    3. views icon 11 views
  7. Which example correctly demonstrates polynomial subtraction?A. (2x^2 + 6x + 1) – (3x^2 + 3x + 9) = 5x^2 + 9x + 10 B. (2x^2 +
    1. answers icon 1 answer
    2. views icon 20 views
  8. Which example correctly demonstrates polynomial addition?A. (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = -x^2 + 3x – 8 B. (2x^2 + 6x +
    1. answers icon 1 answer
    2. views icon 22 views
  9. Which example correctly demonstrates polynomial subtraction?(2x2+6x+1)−(3x2+3x+9)=x2+3x+8 (2x2+6x+1)−(3x2+3x+9)=5x2+9x+10
    1. answers icon 1 answer
    2. views icon 14 views
  10. Which example correctly demonstrates polynomial addition?A. (2x^2+6x+1) + (3x^2+3x+9)=-x^2+3x-8 B. (2x^2+6x+1) + (3x^2+3x+9)=
    1. answers icon 1 answer
    2. LAYLA M asked by LAYLA M
    3. views icon 10 views